1999
DOI: 10.1159/000007677
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Protects against Pancreatic Damage in Cerulein-Induced Pancreatitis

Abstract: Epidermal growth factor (EGF) exhibits gastroprotective and ulcer-healing action. These observations prompted us to determine the influence of EGF on cerulein-induced pancreatitis (CIP) in the rat. Acute pancreatitis was induced by subcutaneous infusion of cerulein (10 μg/kg/h) for 5 h. Initially EGF was administrated twice at doses of 1, 5, 10 or 100 μg/kg s.c. (first injection 30 min prior to cerulein infusion, and the second injection 2.5 h after the start of cerulein infusion) and from this part of study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The EGFR signalling pathway plays a key role in protecting against caerulein-evoked pancreatic damage 30 31. EGF family ligands can bind to the extracellular domain of EGFR and induce phosphorylation at specific tyrosine residues within the receptor cytoplasmic domain.…”
Section: Resultsmentioning
confidence: 99%
“…The EGFR signalling pathway plays a key role in protecting against caerulein-evoked pancreatic damage 30 31. EGF family ligands can bind to the extracellular domain of EGFR and induce phosphorylation at specific tyrosine residues within the receptor cytoplasmic domain.…”
Section: Resultsmentioning
confidence: 99%
“…EGFR activation by either EGF or betacellulin has been shown to protect against development of acute pancreatitis, in association with pancreatic cell proliferation, decreased inflammatory cytokine/chemokine production, and maintenance of blood flow to the pancreas (113,309,550,590). However, EGFR activation is also implicated in the development of pancreatic fibrosis resulting from chronic pancreatitis.…”
Section: B Egfr Signaling and Pancreas Injury And Fibrosismentioning
confidence: 99%
“…Animal studies have shown that growth factors which include EGF, along with hepatocyte growth factor (HGF) and insulin-like growth factor-1 (IGF-1), attenuate the pancreatic damage following an attack of AP [9,18,19]. EGF is a powerful mitogen, which modulates pancreatic secretion and stimulates pancreatic growth [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, EGF molecules bind to such receptors on the acinar cells and promote pancreatic regeneration and recovery [8]. When administered before and during the induction of cerulein-induced pancreatitis in rats, EGF protects against pancreatic damage [9]. In acute necrotizing pancreatitis animal models, treatment with EGF prevents the development of septic complications [10].…”
Section: Introductionmentioning
confidence: 99%